Correction: Tran et al. Antimicrobial Properties of Bacillus Probiotics as Animal Growth Promoters. Antibiotics 2023, 12, 407 - Charlie Tran; Darwin Horyanto; Dragana Stanley; Ian E. Cock; Xiaojing Chen; Yunjiang Feng (MDPI AG, 2023)
In the original publication [...]